On the criteria of transversality and disjointness of nonnegative selfadjoint extensions of nonnegative symmetric operators - Kovalev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We propose criteria of transversality and disjointness for the Friedrichs and Krein extensions of a nonnegative symmetricoperator in terms of the vectors $\{ φ j , j \in J\}$ that form a Riesz basis of the defect subspace. The criterion is applied tothe Friedrichs and Krein extensions of the minimal Schr¨odinger operator $\scr A$ d with point potentials. We also present a newproof of the fact that the Friedrichs extension of the operator $\scr A$ d is a free Hamiltonian.